From Agreements to Consensus - Cortés-Reyes, Edgar (Colombian Journal of Anesthesiology, 2012)
In the light of the diversity and complexity of medical knowledge and considering the lack of sufficient evidence for health-related decision-making, medical professionals usually seek agreements. Though it may seem an apparently simple task, the idea is to understand that this is a high-level process. Assuming consensus is a rigorous multidisciplinary research methodology that, in addition to overcoming any conceptual gaps, systematically generates new knowledge via formal rounds of consultation. This article is intended to set forth a position with regards to the rigorous approach followed for health related consensus. A popular methodology is discussed - Delphi - identifying its advantages and steps followed, including its modifications and uses according to the researchers' needs and resources, keeping in mind the importance of considering the final result expressed in the recommendations in terms of its fundamental impact on health related issues.